2014
DOI: 10.1186/1471-2369-15-153
|View full text |Cite
|
Sign up to set email alerts
|

A multinational phase IIb/III trial of beraprost sodium, an orally active prostacyclin analogue, in patients with primary glomerular disease or nephrosclerosis (CASSIOPEIR trial), rationale and study design

Abstract: BackgroundChronic kidney disease (CKD) is public health concern even in Asian countries. TRK-100STP, a sustained release tablet of an orally-active prostacyclin analogue, beraprost sodium, is suggested to suppress worsening of some parameters of renal filtration function, containing in slope of 1/serum creatinine (1/SCr) vs. time in a phase II clinical trial.Methods/designWe describe the design of the phase IIb/III trial of TRK-100STP, CASSIOPEIR (CRF Asian Study with Oral PGI2 derivative for Evaluating Improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Based on the findings of this trial, we have further been conducting a phase IIb/III trial, CASSIOPEIR ( C RF As ian S tudy w i th O ral P GI 2 derivative for E valuating I mprovement of R enal function) [ 42 ]. This new trial will enroll patients who have more severe disease than those enrolled in this trial in order to ensure that a sufficient number of clinical events can be observed within a designated time period, using renal composite endpoints to evaluate treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of this trial, we have further been conducting a phase IIb/III trial, CASSIOPEIR ( C RF As ian S tudy w i th O ral P GI 2 derivative for E valuating I mprovement of R enal function) [ 42 ]. This new trial will enroll patients who have more severe disease than those enrolled in this trial in order to ensure that a sufficient number of clinical events can be observed within a designated time period, using renal composite endpoints to evaluate treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol of the CASSIOPEIR study was previously reported [ 18 ]. To summarize, this study was a multicenter, randomized, double‐blind, placebo‐controlled comparative study of TRK‐100STP (120 or 240 μg/day) in non‐diabetic CKD patients with primary glomerular disease or nephrosclerosis.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of primary glomerular disease was the same as in our previous Ph‐II study [ 17 ], and was specified in the protocol. In addition, secondary glomerular diseases such as diabetic nephropathy, lupus nephritis, ANCA‐related nephritis, so on, are excluded in the exclusion criteria of the protocol [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 80s and 90s, scientific literature put great emphasis on the prostacyclin system and on the use of prostacyclin analogs in kidney disease (14,35,36). The main application field was ischemic injury, but there are also some reported experiences in the field of transplantation.…”
Section: Discussionmentioning
confidence: 99%